Influência dos parâmetros de síntese de nanofios de prata pelo método poliol - Ono, Rodrigo (2022)
During the last decades, silver nanowires have gained increasing prominence in the scientific community and industry due to their unique properties and promising applications in various fields of electronic devices. Recent studies have shown that devices made of silver nanowire networks have transparency, conductivity and compliance equivalent to or even greater than traditional conductive materials. In this work we investigated the influence of stabilizing salt, molar ratio PVP/AgNO3, molecular mass of PVP as well as their mixtures on the morphology of silver nanowires synthesized by the polyol method The results showed that it is possible to obtain uniform silver nanowires with average diameters of 30 ± 5 nm and high aspect ratios using NaBr as a stabilizing salt and mixtures of PVPs of different molecular weights.